Live in grace, walk in love : a 365-day journey - Goff, Bob (Nelson Books, an imprint of Thomas Nelson, 2019)
"Built on Bob's trademark storytelling and unique way of helping us to see things in a new way, Live in Grace, Walk in Love takes us through an entire calendar year of meditations on how we can step out in love and confidence in every aspect of our lives. More than a tweet, less than a blog post, these devotional readings--accompanied by Scripture--will inspire and galvanize you live a more liberated, love- and life-giving existence than you ever thought possible."--Amazon.com.